STUDY OF INTERACTION BETWEEN LEAD AND GASTRIC MUCOSAL PROTEIN OF RATS WITH FORENSIC TOXICOLOGY APPROACH - Iwan Aflanie; Iskandar Thalib; Eko Suhartono (Berkala Kedokteran, 2017)
Abstract: Recently, forensic toxicology has been an interesting concern, especially in exposing the phenomena associated with the law. Using the forensic toxicology approach, several cases of lead (Pb) poisoning have been widely revealed. In this present study will be investigate the interaction between Pb and amino acid gastric mucosal constituent proteins, especially cysteine and tyrosine groups. This research is a pure experimental research with posttest control group design, which is divided into 4 groups with 6 rats (Rattus novergicus) in each group. Treatment in each group as follows; P0 was control group were given 2 ml of distilled water; P1 = administration of Pb 0.1 g/L; P2 = Pb administration of 1 mg/L; and P3 = Pb administration of 10 g/L for 4 weeks repectively. According to the results, it can be concluded that Pb-Protein interaction tends to binding of Pb-Cysteine rather than Pb-Tyrosine Keywords: Gastric Mucosa, Lead, Protein